IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR (SOP) PADA PENERIMAAN SISWA BARU SMA N 1 KEPAHIANG DALAM MEWUJUDKAN OUT PUT YANG BERKUALITAS - Mashuri Renoldi (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
The results of this study are Based on this research, data  processing,  and data  analysis that researchers do related to the analysis of input factors, nThis, otput,  and  outcome in the implementation of School Based  Management (SBM) at SMAN1 Kepahiang, the writer can conclude  the following points related  with this research  that the presence of input also is not ‘up’ because in reality there are some inputs that have not reached the SNP, for example  on the number of students  in rombel.  The education process in SMAN 1 Kepahiang summarized in the school management process that seeks to involve the entire school community to support  the PBM. Curriculum development at SMAN 1 Kepahiang seek to maximize the PBM in order to become qualified. However  PBM is not maximized  because they have constraints  on the availability of facilities and  infrastructure. The existence  of output  factors, in accordance with the SNP hopes  that maximizes all the competences of the learners.  But in fact the intended target are often distorted  by the fact that happened